2016
DOI: 10.1007/s10554-016-0904-2
|View full text |Cite
|
Sign up to set email alerts
|

Area strain from 3D speckle-tracking echocardiography as an independent predictor of early symptoms or ventricular dysfunction in asymptomatic severe mitral regurgitation with preserved ejection fraction

Abstract: The indication for surgery in asymptomatic severe mitral regurgitation (SMR) with preserved left ventricular ejection fraction (LVEF) is controversial. We sought to study 3D myocardial mechanics in this population and test 3D-speckle tracking (3DST) parameters as possible predictors of events. 45 asymptomatic patients with SMR and LVEF >60 % and 20 control individuals without cardiac disease underwent 3DST echocardiography. MR group additionally underwent further clinical monitoring. Dyspnea, LVEF under 60 %, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Also relatively low temporal and spatial resolution can affect optimal tracking and accurate data acquisition, whereas prior data have shown that myocardial deformation measurements were not compromised by 3D speckle tracking when derived from 18~25 frames/s datasets . While several studies have shown the utility of 3D speckle tracking in various clinical scenarios, clinical implication of 3D speckle tracking is currently being increasingly explored . However, there are limited data regarding the clinical prognostic value of 3D speckle tracking in the patients with acute MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also relatively low temporal and spatial resolution can affect optimal tracking and accurate data acquisition, whereas prior data have shown that myocardial deformation measurements were not compromised by 3D speckle tracking when derived from 18~25 frames/s datasets . While several studies have shown the utility of 3D speckle tracking in various clinical scenarios, clinical implication of 3D speckle tracking is currently being increasingly explored . However, there are limited data regarding the clinical prognostic value of 3D speckle tracking in the patients with acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…have shown the utility of 3D speckle tracking in various clinical scenarios, clinical implication of 3D speckle tracking is currently being increasingly explored [18][19][20][21][22][23][24]. However, there are limited data regarding the clinical prognostic value of 3D speckle tracking in the patients with acute MI.…”
mentioning
confidence: 99%
“…In severe chronic mitral regurgitation (MR), guidelines recommend intervening on symptomatic patients or when LVEF drops (59,60). However, in patients with severe MR and LVEF still within normal range, subclinical LV dysfunction may go unrecognized (61,62). It was demonstrated that 2DSTE-derived LV global longitudinal strain may be useful to identify a maladaptive preloadrelated change associated with the risk for a substantial reduction in LVEF immediately following mitral valve repair (6,63,64).…”
Section: Mitral Valve Diseasesmentioning
confidence: 99%
“…It was demonstrated that 2DSTE-derived LV global longitudinal strain may be useful to identify a maladaptive preloadrelated change associated with the risk for a substantial reduction in LVEF immediately following mitral valve repair (6,63,64). At present, few studies (62,65,66) have looked at the role of 3DSTE in patients with MR. In patients with MR with preserved LVEF, 3D area strain was shown to be an independent predictor of early symptoms or LV dysfunction (62).…”
Section: Mitral Valve Diseasesmentioning
confidence: 99%
“…Deformation imaging has already proven its value in, for example, hypertrophic cardiomyopathy (Fuster, Van Der Zee, & Miller, 2009) and valvular heart disease (Casas-Rojo et al, 2016;Gunjan, Kurien, & Tyagi, 2012), in which deterioration of deformation parameters can be observed before LVEF decreases. This apparent superior sensitivity for changes in cardiac function makes deformation imaging of great potential use within cardiac regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%